2003
DOI: 10.1002/eqe.275
|View full text |Cite
|
Sign up to set email alerts
|

Design of yielding metallic and friction dampers for optimal seismic performance

Abstract: SUMMARYThis paper deals with the optimal design of yielding metallic dampers and friction dampers together as they both have similar design characteristics and parameters. Ample tests and analytical studies have conÿrmed the e ectiveness of these energy dissipation devices for seismic response control and protection of building structures. Since these devices are strongly non-linear with several parameters controlling their behaviour, their current design procedures are usually cumbersome and not optimal. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(63 citation statements)
references
References 20 publications
1
61
0
1
Order By: Relevance
“…(1). The damper consists of first level board (1), front side board (2), right moving rod (3), super elastic SMA wire (4), left moving rod (5), friction plate (6), second level board (7), back side board (8), high strength bolt (9), wire wrapped implement (10), fixed screw (11), connecting bolt (12), sleeve (13), fixture (14) and PTFE sheet (15). Numbers in brackets correspond to the each element of the damper shown in Fig.…”
Section: Structure Of Sma-friction Dampermentioning
confidence: 99%
“…(1). The damper consists of first level board (1), front side board (2), right moving rod (3), super elastic SMA wire (4), left moving rod (5), friction plate (6), second level board (7), back side board (8), high strength bolt (9), wire wrapped implement (10), fixed screw (11), connecting bolt (12), sleeve (13), fixture (14) and PTFE sheet (15). Numbers in brackets correspond to the each element of the damper shown in Fig.…”
Section: Structure Of Sma-friction Dampermentioning
confidence: 99%
“…A variety of friction dissipators have been proposed for structural energy dissipation (Pall and Marsh 1982, Palsson et al 1984, Tyler 1985, Sumitomo 1987, Pall 1989, Richter et al 1990, Vezina et al 1992, Cherry and Filiatrault 1993, Grigorian et al 1993, Way 1996, Soong and Dargush 1997, Housner et al 1997, Wu and Ou 2003, Cho and Kwon 2004, Morgen and Kurama 2004, Tsai et al 2008, Morgen and Kurama 2008, design criteria have been issued (Rao et al 1996, Colajanni and Papia 2008, Levy et al 2000, Moreschi and Singh 2003, De la Llera et al 2005, Levy, Lavan and Rutenberg 2005, numerical simulation algorithms have been formulated (Dimova et al 1995, De la Cruz et al 2007) and a number of applications have been reported (Pall et al 1993, Tena 2007, Zhou et al 2007). In the reference (Dimova and Hirata 2000) a study about the seismic efficiency of friction dissipators is presented.…”
Section: Fig 2 Hysteresis Loops Of Energy Dissipatorsmentioning
confidence: 99%
“…In this paper, the relative performance index (RPI) [21] that reflects the structural strain energy is selected as a target, expressed by Eq. (27), to be minimized, considering the relation between the amounts of elastic strain energy imparted into a building and the resulting structural response:…”
Section: Selection Of Parametersmentioning
confidence: 99%